Early experiments with hypothermic oxygenated machine perfusion of kidney grafts from extended criteria donors - A. V. Shabunin; M. G. Minina; P. V. Drozdov; I. V. Nesterenko; D. A. Makeev; O. S. Zhuravel; L. R. Karapetyan; S. A. Astapovich (Вестник трансплантологии и искусственных органов, 2022)
Objective: to evaluate the safety and efficacy of hypothermic oxygenated machine perfusion (HOPE) for kidney grafts obtained from expanded criteria donors (ECD).Materials and methods. From June 2018 to June 2021, 200 surgeries involving kidney transplants from deceased donors were performed at Botkin City Clinical Hospital. Of these, 123 were men (61.5%) and 77 were women (38.5%). The mean age was 47.62 ± 11.69 (20–73) years. In 102 cases, kidney grafts were procured from ECD. In 92 recipients (90.2%) of kidney transplants from an expanded criteria donor, static cold storage done according to the standard technique was used to preserve the organ; these patients constituted observation group 1. In 10 recipients (9.8%), hypothermic oxygenated perfusion was used in addition to static cold preservation; these patients formed observation group 2.Results. No 30-day mortality was recorded in both observation groups. The mean static cold storage time in group 1 patients was 612.33 ± 178.88 (133–1180) minutes. Overall incidence of delayed graft function was 26.5% (53/200). Incidence of delayed graft function was 19.3% (19/98) for organs from standard donors using static cold storage and 35.8% (33/92) for ECD organs. Twenty-five patients (12.5%) had postoperative complications. Postoperative complications with delayed graft function were diagnosed in 12 patients, which was 22.6% (12/53), with immediate function in 13 patients, which was 8.8% (13/147). Mean cold storage time in group 2 patients was 319.11 ± 110.24 (311–525) minutes. Mean HOPE time was 202.34 ± 21.48 (150–210) minutes. Delayed graft function was recorded in 1 group 2 patient (10%). No complications, including perfusion-related one, were recorded in this group.Conclusion. The unique technique used at Botkin City Clinical Hospital for HOPE in kidney transplant is safe. It provides a low risk of delayed graft function for ECD kidneys.